1995
DOI: 10.1021/jm00014a019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 5-Fluoro-2'-deoxyuridine Phosphoramidate Analogs

Abstract: A series of alkylating phosphoramidate analogs of 5-fluoro-2'-deoxyuridine has been prepared and their growth inhibitory activity evaluated against murine L1210 leukemia and B16 melanoma cells in vitro. These compounds were designed to undergo intracellular release of the phosphoramidate anions, which it was hoped would function as irreversible inhibitors of thymidylate synthase. The expectation was that binding of the nucleoside moiety would be followed by alkylation of the enzyme via the phosphoramidate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…121 Based on their earlier observation that perhydrooxazine derivatives of aldophosphoramides were prodrugs of phosphoramide mustard, Borch and co-workers constructed perhydrooxazine phosphoramidate diesters of FUdR and substituted ethyl amines and evaluated their anticancer activity. 121,150 Mechanistic studies revealed that the compounds decomposed rapidly in aqueous media to the corresponding phosphoramidate monoester, followed by formation of aziridinum phosphoramidate. Subsequent attack of the electrophilic aziridium phosphoramidate by water resulted in release of FUdR monophosphate.…”
Section: Phosphoramidate Diestersmentioning
confidence: 99%
See 2 more Smart Citations
“…121 Based on their earlier observation that perhydrooxazine derivatives of aldophosphoramides were prodrugs of phosphoramide mustard, Borch and co-workers constructed perhydrooxazine phosphoramidate diesters of FUdR and substituted ethyl amines and evaluated their anticancer activity. 121,150 Mechanistic studies revealed that the compounds decomposed rapidly in aqueous media to the corresponding phosphoramidate monoester, followed by formation of aziridinum phosphoramidate. Subsequent attack of the electrophilic aziridium phosphoramidate by water resulted in release of FUdR monophosphate.…”
Section: Phosphoramidate Diestersmentioning
confidence: 99%
“…In addition, although studies with thymidine kinase-de®cient cells were not reported, thymidine antagonism studies supported a mechanism based on FUdR monophosphate release and not direct inhibition of thymidylate synthase. 121 Studies of the in vivo antiviral or anticancer potency of phosphoramidate diesters have not been reported. As observed for the cycloSal nucleoside phosphotriesters, phosphotriester diastereomers can exhibit differences in biological potency.…”
Section: Phosphoramidate Diestersmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of recent literature shows that 2 H -1,3-oxazine derivatives exhibit various types of bioactivity, e.g., herbicidal [12], inhibition of cell growth and enzyme activity [13–18], inhibition of voltage-gated sodium channels [19] and metabotropic glutamate receptor-5a (hmGluR5a) [20]. Consequently, our second aim was to extend the reaction to the preparation of aryl- and halogen-substituted 1,3-oxazines, taking into account that the latter are potential candidates for metal-catalyzed couplings and thus allow further modifications.…”
Section: Introductionmentioning
confidence: 99%
“…A number of strategies have been investigated to overcome the low efficacy and development of resistance to FDU. Since ionic nucleotides penetrate cells poorly and are readily dephosphorylated extracellulary, the development of lipophilic neutral masked nucleotide prodrugs that can cross the cell membrane and potentially liberate the nucleotide intracellularly has been investigated extensively [10][11][12][13][14][15] . Esters of FDU have also been widely investigated [16][17][18] .…”
mentioning
confidence: 99%